Circular RNAs in gynecologic cancers: mechanisms and implications for chemotherapy resistance - Qin, Meiying; Zhang, Chunmei; Li, Yang (Frontiers in Pharmacology, 2023)
Chemotherapy resistance remains a major challenge in the treatment of gynecologic malignancies. Increasing evidence suggests that circular RNAs (circRNAs) play a significant role in conferring chemoresistance in these cancers. In this review, we summarize the current understanding of the mechanisms by which circRNAs regulate chemotherapy sensitivity and resistance in gynecologic malignancies. We also discuss the potential clinical implications of these findings and highlight areas for future research. CircRNAs are a novel class of RNA molecules that are characterized by their unique circular structure, which confers increased stability and resistance to degradation by exonucleases. Recent studies have shown that circRNAs can act as miRNA sponges, sequestering miRNAs and preventing them from binding to their target mRNAs. This can lead to upregulation of genes involved in drug resistance pathways, ultimately resulting in decreased sensitivity to chemotherapy. We discuss several specific examples of circRNAs that have been implicated in chemoresistance in gynecologic cancers, including cervical cancer, ovarian cancer, and endometrial cancer. We also highlight the potential clinical applications of circRNA-based biomarkers for predicting chemotherapy response and guiding treatment decisions. Overall, this review provides a comprehensive overview of the current state of knowledge regarding the role of circRNAs in chemotherapy resistance in gynecologic malignancies. By elucidating the underlying mechanisms by which circRNAs regulate drug sensitivity, this work has important implications for improving patient outcomes and developing more effective therapeutic strategies for these challenging cancers.